Legionella pneumophila serogroup 5 infection in the presence of multiple environmental contamination. The importance of a bacteriological diagnosis (Italian Journal of Public Health, 2007)
Legionella pneumophila is a pathogen that causes severe pneumonia in humans; L. pneumophila serogroup 1 accounts for at least 90% of infections. This is not linked to an environmental predominance of Legionella pneumophila 1, but may be due to a greater virulence of the strain. L. pneumophila sg 5 has also been reported, albeit less frequently, to be a cause of the disease. We report a case of L. pneumophila sg 5 occurring in a large hospital in southern Italy (Apulia region), where both L. pneumophila sg 1 and sg 5 were detected in the water supply; the nosocomial origin was demonstrated by molecular subtyping (PFGE). An environmental investigation, performed immediately after diagnosis of the case of legionellosis, identified a ow L. pneumophila sg 5 contamination level. Our experience highlights that in hospital, risk assessment, in rder to institute control measures for Legionella, should be carried out not only in response to a case of the disease and/or in risk wards only, as described in the Italian Guidelines, but periodically in every ward. The present study confirms that, although in the community L. pneumophila sg 1 is the most frequent strain isolated in both outbreaks and isolated cases, in hospital other serogroups and species may often cause infection because of the high susceptibility of the hosts.
Keywords: Legionella spp; legionellosis; bacteriological diagnosis; epidemiology